Evaluate the structural and thermal analysis of solid and cross drilled rotor by using finite element analysis. (2021) - Jule, Leta Tesfaye; Krishnaraj, Ramaswamy; Nagaprasad, Nagaraj; Stalin, B.; Vignesh, V.; Amuthan, Tamilselvan
Abstract: The finite element analysis (FEA) in the brake rotor is essential to study the thermal behavior of the model. In the brake disc, the frictional contact between the brake disc and brake pad will generate heat. The heat generated will cause adverse effects such as thermal judder, hot spots. Hence the temperature distribution over the disc rotor has been a primary concern in research. The thermal behavior over the disc can cause an adverse effect on the rotor failure. Thus the material, design are mainly focused on many kinds of research. The cross-drilled rotors have been compared with the solid rotor with three different materials, which has shown the best possible combination with the design and material compatibility. The objective is to study the materials' thermal behavior with a solid disc and the cross-drilled rotor to optimum design. The geometry was modelled in PRO-E software, and the analysis was done in ANSYS software. The results obtained by the simulation have been compared. Three materials with different properties have been designed with solid and cross-drilled rotors. By the analysis, cross-drilled disc performance has produced the best optimum results.